2022
DOI: 10.1007/s10142-022-00843-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the TF-miRNA-mRNA co-regulatory networks involved in sepsis

Abstract: Identification of the TF-miRNA-mRNA co-regulatory networks involved in sepsis

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Meanwhile, miRNA expression is also mediated by TF, thus forming a complex upstream and downstream regulatory network of miRNA, namely TF-miRNA-mRNA (40,41). TF-miR-NA-mRNA could help correlate the interaction of transcription factors, miRNA and target genes together, and visualize a network map, thus exploring potential key molecules more intuitively and conveniently (42,43). In this study, the TF-miRNA-mRNA network construction results identified that RB1, RBCA1 and JDP2 regulated DDIT3, besides, RELA, ABL1 and NFKB1 regulated FOXO3.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, miRNA expression is also mediated by TF, thus forming a complex upstream and downstream regulatory network of miRNA, namely TF-miRNA-mRNA (40,41). TF-miR-NA-mRNA could help correlate the interaction of transcription factors, miRNA and target genes together, and visualize a network map, thus exploring potential key molecules more intuitively and conveniently (42,43). In this study, the TF-miRNA-mRNA network construction results identified that RB1, RBCA1 and JDP2 regulated DDIT3, besides, RELA, ABL1 and NFKB1 regulated FOXO3.…”
Section: Discussionmentioning
confidence: 99%